Bergmann's and Allen's Rules in Native European and Mediterranean Phasmatodea - Shelomi, Matan; Zeuss, Dirk (Frontiers in Ecology and Evolution, 2017)
Bergmann’s rule states that organisms at higher latitudes should be larger and thicker than those closer to the equator to better conserve heat, and Allen’s rule states that they will have shorter and thicker limbs at higher latitudes. Alternative explanations for latitudinal size clines include plant productivity and seasonality. The rules generally hold in endotherms, but in insects different species within the same genus can respond to latitude in unpredictable ways. We present the first biogeographical analysis of these rules in stick insects (order Phasmatodea), using four European species. Their long and thin bauplan makes the Phasmatodea ideal for ecomorphological studies of body length, which could identify the evolutionary drivers of their remarkable size range (including the world’s longest insects). Using preserved specimens from collections across Europe; body segment and limb measurements were taken for both genders of the species Bacillus rossius, Clonopsis gallica, Leptynia attenuata, and Pijnackeria hispanica. Lengths and volumetric features were compared to latitude as well as annual mean temperature, net primary productivity, and annual growing degree days, using weighted linear regressions and ANOVA analyses. At lower latitudes / higher temperatures, B. rossius and L. attenuata had longer limbs [Allen clines] and were larger bodied and/or longer [converse-Bergmann clines], while the other species did not show latitudinal clines per se. This matches what was predicted based on closely related insects and the presence of large Phasmatodea in the tropics, but violates the temperature-size rule. Most variation in size could be attributed to temperature, but untested factors could also play a role Whether these ecogeographic rules hold true for tropical Phasmatodea and whether genetics or environment play are more important in determining adult length are topics for future research.